Yale Global Tic Severity Scale (YGTSS): Psychometric Quality of the Gold Standard for Tic Assessment Based on the Large-Scale EMTICS Study - Martina Haas; Ewgeni Jakubovski; Carolin Fremer; Andrea Dietrich; Pieter J. Hoekstra; Burkard Jäger; Kirsten R. Müller-Vahl; The EMTICS Collaborative Group; Alan Apter; Valentina Baglioni; Juliane Ball; Noa Benaroya-Milshtein; et al. (Frontiers in Psychiatry, 2021)
The Yale Global Tic Severity Scale (YGTSS) is a clinician-rated instrument considered as the gold standard for assessing tics in patients with Tourette's Syndrome and other tic disorders. Previous psychometric investigations of the YGTSS exhibit different limitations such as small sample sizes and insufficient methods. To overcome these shortcomings, we used a subsample of the large-scale “European Multicentre Tics in Children Study” (EMTICS) including 706 children and adolescents with a chronic tic disorder and investigated convergent, discriminant and factorial validity, as well as internal consistency of the YGTSS. Our results confirm acceptable convergent and good to very good discriminant validity, respectively, indicated by a sufficiently high correlation of the YGTSS total tic score with the Clinical Global Impression Scale for tics (rs = 0.65) and only low to medium correlations with clinical severity ratings of attention deficit/hyperactivity symptoms (rs = 0.24), obsessive–compulsive symptoms (rs = 27) as well as internalizing symptoms (rs = 0.27). Internal consistency was found to be acceptable (Ω = 0.58 for YGTSS total tic score). A confirmatory factor analysis supports the concept of the two factors “motor tics” and “phonic tics,” but still demonstrated just a marginal model fit (root mean square error of approximation = 0.09 [0.08; 0.10], comparative fit index = 0.90, and Tucker Lewis index = 0.87). A subsequent analysis of local misspecifications revealed correlated measurement errors, suggesting opportunities for improvement regarding the item wording. In conclusion, our results indicate acceptable psychometric quality of the YGTSS. However, taking the wide use and importance of the YGTSS into account, our results suggest the need for further investigations and improvements of the YGTSS. In addition, our results show limitations of the global severity score as a sum score indicating that the separate use of the total tic score and the impairment rating is more beneficial.